Model of runtime memory leak detection based on the virtual machine introspection - Ru-liang XIAO; Jun JIANG; You-cong NI; Xin DU; Guo-qing XIE; Sheng-zhen CAI (Tongxin xuebao)
Virtualization technology has been widely used in the field of cloud computing and data center, and it is an important way to improve reliability of system under the virtual computing environment using runtime memory leak de-tecting to eliminate memory leaks. A model of runtime memory leak detection based on the virtual machine introspection and an approach to predication on memory leak were proposed. The prototype system of the model was designed and im-plemented. By analyzing and evaluating effectiveness and performance of the prototype system, the results show that these models and methods can effectively detect memory leaks, and have better performance.